1986
DOI: 10.1177/000331978603700810
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction After Acute Carbon Monoxide Poisoning: Case Report

Abstract: A 28-year-old man with acute myocardial infarction after carbon monoxide poisoning is reported. He had chest pain after the exposure to carbon monoxide. The electrocardiogram, serum enzymes, and technetium-99m pyrophosphate scintigrams showed anterior myocardial infarction. The coronary angiogram, which was performed one month after the onset, showed no visible atherosclerotic lesion. As to the cause of myocardial infarction, it is assumed that carbon monoxide reduced the oxygen supply to the myocardium and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…Most of the recent literature focuses on ST elevation and T wave inversions in patients with CO poisoning. 7,8,9,10 Contrary to this, our patient did not exhibit any EKG changes at any point during his hospital course. It is reported that other cardiac groups may not show any ischemic changes on EKG.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Most of the recent literature focuses on ST elevation and T wave inversions in patients with CO poisoning. 7,8,9,10 Contrary to this, our patient did not exhibit any EKG changes at any point during his hospital course. It is reported that other cardiac groups may not show any ischemic changes on EKG.…”
Section: Discussioncontrasting
confidence: 88%
“…6 The trend of elevation in serum troponin levels in our patient was similar to the trend previously reported, which spans from 2-8 hours. 1,7,8 The rise in troponin levels correlates to the half life of CO in patients. It has been reported that CO has a half life of 300 minutes if the patient is breathing room air, though this is decreased to 90 minutes with use of a non-breather mask and 30 minutes if hyperbaric oxygen treatment is provided.…”
Section: Discussionmentioning
confidence: 99%
“…CO may make the endothelial cell relatively hypoxic, a powerful stimulus of prostacyclin (PGI 2 ) production, or less likely exert a direct toxic effect on the endothelial cells [23]. Furthermore, survivors of CO exposure may present a clinical pattern of ischemic heart disease [24,25,26] which can be recovered by hyperbaric oxygenation treatment [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Chest discomfort or pain can be resulted from myocardial ischemia or necrosis in the presence and in the absence of coronary artery disease. [10][11][12] Shortness of breath and low blood pressure can be symptoms of cardiac dysfunction. 13) In this patient, shortness of breath and tachycardia were noted at the time of admission and these symptoms suggesting the presence of cardiac dysfunction.…”
Section: D a Bmentioning
confidence: 99%